Metode Ctl (Contextual Teaching And Learning) Dalam Meningkatka N Hasil Belajar Agama Islam Siswa Di Sd Negeri 010097 Kisaran - Humairoh, Lailan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to see the improvement of students' learning outcomes of Islam in the sub-chapters of the Qur'an and Hadith in the material Achieving fortune with endeavors at SD Negeri 010097 Kisaran, Asahan Regency, North Sumatra Province by using contextual teaching learning (CTL). The research model used is classroom action research (CAR) with two cycles. The results of this study found that the contextual teaching learning model improves student PAI learning outcomes in the matter of Achieving a fortune with Effort through the implementation of 2 cycles. In the first cycle, 56.66% of students completed this material, because they did not meet the minimum completeness, the second cycle was carried out and in the second cycle, the percentage of students who completed 80% was more than 5% from the minimum 75%.